2019
DOI: 10.1021/jacs.9b05182
|View full text |Cite
|
Sign up to set email alerts
|

Golden Opportunity: A Clickable Azide-Functionalized [Au25(SR)18] Nanocluster Platform for Interfacial Surface Modifications

Abstract: Ultrasmall atomically precise monolayerprotected gold thiolate nanoclusters are an intensely researched nanomaterial framework, but there is a lack of a system that can be directly synthesized and undergo interfacial surface chemistry. We report an [Au 25 (SCH 2 CH 2 -p-C 6 H 4 -N 3 ) 18 ] − nanocluster platform with azide moieties appended onto each surface ligand. The structure of this surface reactive cluster has been confirmed by single-crystal X-ray crystallography, mass spectrometry and ultraviolet visib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 29 publications
(40 reference statements)
1
49
0
Order By: Relevance
“…Table 2 lists the magic Au clusters having the cores of Au 4 (2e), Au 11 (8e), Au 13 (8e), Au 79 (58e), Au 107 (81e), and Au 114 (84e). [ 9–62 ] The ubiquitous nature of Au 4 (2e), Au 11 (8e) and Au 13 (8e) regardless of the ligands, indicates their inherent stability. SCXRD analyses showed that the metallic cores take isotropic structures such as icosahedron (Ih) and decahedron (Dh) (Table 2).…”
Section: Effect Of Size: Spherical Superatomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 lists the magic Au clusters having the cores of Au 4 (2e), Au 11 (8e), Au 13 (8e), Au 79 (58e), Au 107 (81e), and Au 114 (84e). [ 9–62 ] The ubiquitous nature of Au 4 (2e), Au 11 (8e) and Au 13 (8e) regardless of the ligands, indicates their inherent stability. SCXRD analyses showed that the metallic cores take isotropic structures such as icosahedron (Ih) and decahedron (Dh) (Table 2).…”
Section: Effect Of Size: Spherical Superatomsmentioning
confidence: 99%
“…When the degree of distortion exceeds a critical level, the superatom transforms into a structural isomer which has distinctly different atomic packings. Namely, the superatomic cores of [(Au/Ag) x L y ] z can take isomeric structures depending on their relative stabilities determined by the nature of L. Au 13 (8e) generally prefers an Ih structure as demonstrated in Table 2, [ 17,37–55 ] but takes a face‐centered cubic (FCC)‐based structure in [Au 23 (S c Hex) 16 ] − ( c HexSH = cyclohexanethiol), Au 24 (SAdm) 16 (AdmSH = 1‐adamantanethiol), and [Au 25 (SPG) 18 ] − (PGSH = N ‐(2‐mercaptopropionyl)glycine) ( Figure a). [ 177–179 ] The formation of an FCC Au 13 (8e) superatom is ascribed to the steric repulsion between the thiolate ligands having a bulky α‐carbon.…”
Section: Effect Of Shape: Nonspherical Superatomsmentioning
confidence: 99%
“…The resulting polymers were precipitated to form nanoparticles and used for in vitro and in vivo imaging. Using smaller nanostructures, Workentin and co‐workers showed that modification of ligands on gold nanoclusters can be carried out using SPAAC [76] . The gold clusters were stabilized with a library of 18 different azide‐functionalized thiol ligands, which subsequently underwent a quantitative reaction with ( Z )‐cyclooct‐1‐ene‐5‐yne.…”
Section: Polymer Side‐chain and End‐group Functionalizationmentioning
confidence: 99%
“…Using smaller nanostructures, Workentin andc o-workerss howed that modification of ligandso ng old nanoclusters can be carried out using SPAAC. [76] The gold clusters were stabilized with al ibrary of 18 different azide-functionalized thiol ligands, which subsequently underwent aq uantitative reaction with (Z)-cyclooct-1-ene-5-yne. In addition to nanoparticles,t he surfaceo f block copolymer micelles has been decorated with 4-dibenzocyclooctynol to enable further functionalization with various azide-modified structures via SPAAC.…”
Section: Polymer Side-chain and End-groupfunctionalizationmentioning
confidence: 99%
“…[120] In 2019, Workentin and co-workers reported the synthesis of (Z)-cyclooctene-5-yne (115) (116). [121] With the azide group on the surface of the nanoparticles, it allows for postassembly modifications of these. Due to the highly strained nature of 115, the reaction is complete in under 5 minutes in different solvents, giving the triazole 117 in 96 % yield.…”
Section: Cycloalkenynesmentioning
confidence: 99%